356 Microbial origins in the developmental programming of offspring health - Jašarević, Eldin (J Anim Sci, 2020)
Adverse parental lifetime experiences, such as stress and malnutrition, are implicated in the risk for offspring metabolic, cardiovascular, and neurodevelopmental disorders. In recent years, the maternal microbiome has emerged as an important factor that affects maternal health and infant development during pregnancy and beyond. Using mouse models of maternal stress experience during pregnancy, we examined the hypothesis that maternal stress experience alters the composition of the maternal microbiota and this altered community is transmitted to offspring to mediate effects of prenatal stress. As maternal stress exposure exhibits disruptive effects on both in utero environment and maternal microbiota, it has been difficult to assess the mechanistic involvement of the maternal microbiome to the prenatal stress phenotype independent of stress effects on the fetal environment. To circumvent this, we developed a maternal microbiota transplantation method in which embryonic day 18.5 mouse pups were delivered by caesarean section, thereby preventing natural colonization, and then transplanted with various maternal microbiota communities via orogastric gavage. Transplantation of maternal microbiota from stressed dams into naïve pups delivered by caesarean section recapitulated phenotypes that resembled those seen in prenatally stressed males, including reduced body weight and increased neuroendocrine response to acute stressors. However, transplantation of control maternal vaginal microbiota into prenatally stressed pups delivered by caesarean section did not rescue the prenatal stress phenotype. We showed that the inability to rescue the prenatal stress phenotype is related to transcriptional reprogramming to pathways involved in the regulation of innate immunity in the fetal gut and brain prior to birth and colonization by maternal microbiota. These results are interesting in light of recent studies demonstrating a critical role of the maternal microbiome on homeostasis of immune cell populations in the offspring brain. As an important requirement for normal growth and development, metabolites produced by the maternal gut microbiota cross the placental barrier and gain access to fetal circulation. Thus, we examined the hypothesis that maternal stress experience during pregnancy significantly alters the availability of maternal gut microbiota-derived metabolites, thereby shifting the availability of these metabolites required for the developing brain. Metabolomic profiling of the maternal compartment and fetal brain showed stress-induced reduction in a class of microbiota-derived metabolites involved in immune homeostasis and chromatin remodeling. Indeed, functional profiling of immune populations in the fetal brain revealed an association between reduced metabolite availability and increased infiltration of proinflammatory monocytes in the fetal brain. Further, as the gut microbiome is fairly accessible within clinical settings, we are now also asking how our mouse model translates to humans in a cohort of pregnant women exposed to childhood adversity. Collectively, our results suggest that intergenerational transmission of stress exposure occur via the maternal microbiota through two novel mechanisms. First, stress alterations during pregnancy impact the available pool of maternal gut microbiota-derived metabolites necessary for normal prenatal growth and development. Second, transmission of stress-altered vaginal microbiota may alter critical immune and metabolic processes underlying neurodevelopment.